Associations between leisure time activities and substance use among adolescents in Iceland - Margrét Lára Guðmundsdóttir 1984- (2021)
Verkefnið er lokað til 01.05.2022. This research is a secondary analysis of the Icelandic data from The European School Survey Project on Alcohol and other Drugs (ESPAD) collected in 2019. The ESPAD study has gathered data every four years on school children aged fifteen and sixteen since 1995 from over 40 European countries with Iceland having participated since the beginning (espad.org). The goal of this research is to investigate how different types of leisure activities done almost daily affect substance use in Icelandic adolescents. Substance use being the use of tobacco products (cigarettes, vaping, snuff and snus), alcohol consumption, having been drunk, and having used Cannabis. The hypotheses being that reading for pleasure, and doing hobby activities, almost daily would decrease the likelihood of using substances, going out at night and using the internet for leisure almost daily would increase the likelihood of having tried substances, participating in sports and/or exercise would decrease the likelihood of using tobacco related substances and cannabis but increase the risk of alcohol consumption and having been drunk, and playing video games almost daily would increase the risk of tobacco related substances and cannabis use but decrease the likelihood of alcohol consumtion and having been drunk. The findings indicated negative associations between substance use and sports participation for both genders, book reading for girls, and hobby partaking in girls. Positive associations were found with going out at night for all substances, and internet use for boys, and some substances. The activities that show the least association with substance use for both genders were sports and or exercising almost every day and the most association was found with going out almost every night. This research is a secondary analysis of the Icelandic data from The European School Survey Project on Alcohol and other Drugs (ESPAD) collected in 2019. The ESPAD study has gathered data every four years on school children ...